Karakteristik Pedagang Buah Perempuan di Pasar Pinasungkulan Karombasan Kecamatan Wanea Kota Bitung - Kapantow, Vanessa Angely; Maweikere, Audrey Julia Maria; Rengkung, Leonardus Ricky (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
This study aims to describe the characteristics of women fruit traders in Pinasungkulan Karombasan Market, Wanea District, Manado City. The data used in this research are primary and secondary data. The analysis used in this research uses descriptive methods that are included in qualitative and for the analysis of income or profit. The results of the research on the age characteristics of women fruit traders in Pinasungkulan Karombasan Market show diversity in the age range ranging from 41 years to 65 years, the level of education ranging from basic education (SD) to undergraduate (S1), the length of business or running a business ranging from 3 years to 36 years, the operational time of traders ranges from 12 hours to 17 hours a day from opening to closing the fruit selling stalls, having a number of dependents of 2 to 7 people, for the origin of fruit supply all types of fruit come from the North Sulawesi region, the origin of the traders' regions namely Manado, Southeast Minahasa, South Minahasa, Tondano, and Siau. The cost of purchasing fruit is Rp 1,000,000 to Rp 15,135,000. The profit of all respondents of fruit traders in Pinasungkulan Market, Wanea District, Manado City amounted to Rp 24,140,250. This shows that the revenue of fruit traders is greater than the total cost, with a total revenue of Rp 91,914,000 compared to the total cost of a smaller amount.